Testing the Seamount Refuge Hypothesis for Predators and Scavengers in the Western Clarion-Clipperton Zone - Leitner, Astrid B.; Drazen, Jeffrey C.; Smith, Craig R. (Frontiers in Marine Science, 2021)
Seamounts are common in all ocean basins, and most have summit depths >3000 m. Nonetheless, these abyssal seamounts are the least sampled and understood seamount habitats. We report results from the first baited camera deployments on abyssal seamounts. Observations were made in the Clarion Clipperton Zone (CCZ), a manganese nodule region stretching from south of Hawaii nearly to Mexico. This zone will likely experience large-scale deep-sea nodule mining in the near future. The Seamount Refuge Hypothesis (SRH) posits that the seamounts found throughout the CCZ provide refugia for abyssal fauna likely to be disturbed by seabed mining, yielding potential source populations for recolonization of mined areas. Here we use baited cameras to test a prediction of this hypothesis, that bait-attending communities are shared between abyssal seamounts and nearby abyssal plains. We deployed two camera systems on three abyssal seamounts and surrounding abyssal plains in three Areas of Particular Environmental Interests (APEIs), designated by the International Seabed Authority as no-mining areas. We found that seamounts have a distinct community, and differences in community compositions were driven largely by habitat type and productivity changes. In fact, community structures of abyssal-plain deployments hundreds of kilometers apart were more similar to each other than to deployments 15 km away on seamounts. Seamount communities were found to have higher morphospecies richness and lower evenness than abyssal plains due to high dominance by synaphobranchid eels or penaied shrimps. Relative abundances were generally higher on seamounts than on the plains, but this effect varied significantly among the taxa. Seven morphotypes were exclusive to the seamounts, including the most abundant morphospecies, Ilyophis arx. No morphotype was exclusive to the abyssal plains; thus, we cannot reject the SRH for the mobile megafaunal predator/scavenging fauna from CCZ abyssal plains. Because seamounts have unique community compositions, including a substantial number of predator and scavenger morphospecies not found on abyssal plains, they contribute to the beta biodiversity of the Clarion-Clipperton Zone, and thus indirect mining impacts on those distinct communities are of concern.